"Gladiator School: Returning Citizens' Experiences with Secondary Violence Exposure in Prison". Issue 5 (3rd July 2020) - Novisky, Meghan A.; Peralta, Robert L.
ABSTRACT: Prison-based violence exposure is a critical area of study, yet the range of secondary (witnessed) violence experiences among incarcerated persons lacks comprehensive development in the literature. Drawing on qualitative data from 30 interviews with previously incarcerated men and women, we examine the extent of secondary violence exposure faced by these individuals. We find that secondary violence was frequently experienced in prison and often took the form of witnessing non-weaponized assaults, weaponized assaults, multi-perpetrator assaults, and homicide. We document the scope and severity of this violence and underscore the importance of including witnessed victimization in future prison-based violence research and interventions.